Carboxylate release as a nutrient‐acquisition strategy in mycorrhizal plant species in phosphorus‐impoverished environments - Wang, Xiao; Yan, Li; Ranathunge, Kosala; Liu, Lele; Guo, Weihua; Dallongeville, Paul; Mou, Zhijian; Kang, Haibin; Lambers, Hans (The Journal of ecology, 2025)
Plants acquire phosphorus (P) in different ways, including using specialised root structures such as cluster roots and mycorrhizal symbioses. However, mycorrhizal fungi are less effective at acquiring P from severely P‐impoverished soils; yet many mycorrhizal plants thrive in such environments. Hence, we studied what nutrient‐acquisition and ‐utilisation strategies allow these species to persist in these habitats. We chose 19 species (from mycorrhizal and non‐mycorrhizal families) from P‐impoverished environments in south‐western Australia. Leaf element concentrations, including P, nitrogen (N) and manganese (Mn), as well as N and carbon (C) stable isotopes, were measured to explore the likely nutrient‐acquisition and ‐utilisation strategies. Leaf Mn concentrations ([Mn]) were used as a proxy for carboxylates released by roots. Subsequently, glasshouse experiments were conducted to measure the root carboxylate release of seedlings of the selected species grown in nutrient solutions. Most mycorrhizal plant species with high leaf [Mn] showed a considerable release of root carboxylates, which mobilise both P and Mn in soil, just like most non‐mycorrhizal Proteaceae with their specialised cluster roots do. The leaf [N] and [P] of arbuscular mycorrhizal species were higher than those of species with cluster roots and ectomycorrhizal species. Arbuscular mycorrhizal plant species exhibited a significantly more negative δ15N than other mycorrhizal species, indicating they accessed more inorganic N, while cluster‐rooted non‐mycorrhizal species had a positive δ15N, indicating they accessed more organic N. Myrtaceae exhibited a less negative δ13C value and higher leaf [Mn] at a drier location, indicating a higher water‐use efficiency. Their higher leaf [Mn] suggests that photosynthesis was reduced less than leaf growth, providing a greater surplus of carbon, which was released as carboxylates from the roots. Synthesis. Many mycorrhizal plant species very likely depended on root carboxylate release to acquire P at the P‐impoverished study sites. Arbuscular mycorrhizal species exhibited a less conservative nutrient‐utilisation strategy with higher leaf [P] than cluster‐rooted non‐mycorrhizal species and accessed more inorganic N. This supports the contention that the non‐mycorrhizal species were not only more efficient at acquiring P but also at using it; their δ15N values indicated that they accessed more organic N. Many mycorrhizal plant species very likely depended on root carboxylate release to acquire P at the P‐impoverished study sites. Arbuscular mycorrhizal species exhibited a less conservative nutrient‐utilisation strategy with higher leaf [P] than cluster‐rooted non‐mycorrhizal species and accessed more inorganic N. This supports the contention that the non‐mycorrhizal species were not only more efficient at acquiring P but also at using it; the δ15N values indicated that they accessed less organic N.